2003
DOI: 10.1016/s0921-5093(03)00137-0
|View full text |Cite
|
Sign up to set email alerts
|

Tensile creep of polycrystalline near-stoichiometric NiAl

Abstract: Long term tensile creep studies were conducted on binary NiAl in the temperature range 700-1200 K with the objectives of characterizing and understanding the creep mechanisms.Inverse and normal primary creep curves were observed depending on stress and temperature. It is concluded that the primary creep of NiAl is limited by dislocation mobility. The stress exponent for creep, n, decreased from 13.9 at 700 K to 5.5 at 1200 K. The true activation energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Amdry 386 showed superior creep properties compared to the Co-based bond coat Amdry 9954. The higher creep strength of β-NiAl, in contrast with the Ni-and Co-containing γ-solid solution phase, at temperatures above 900 • C, is responsible for the better creep resistance [24][25][26]. The higher yttrium content in Amdry 386 compared to Amdry 9954 led to the formation of smaller Y 2 O 3 particles.…”
Section: Discussionmentioning
confidence: 99%
“…Amdry 386 showed superior creep properties compared to the Co-based bond coat Amdry 9954. The higher creep strength of β-NiAl, in contrast with the Ni-and Co-containing γ-solid solution phase, at temperatures above 900 • C, is responsible for the better creep resistance [24][25][26]. The higher yttrium content in Amdry 386 compared to Amdry 9954 led to the formation of smaller Y 2 O 3 particles.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that the creep strengths of monolithic intermetallics are inferior to advanced single crystal nickel-base superalloys [3][4][5] . Although the intermetallics based on the L12-ordered structure are attractive as high temperature structural materials because of their positive temperature dependence of yield strength, "the creep strength anomaly" does not exist in these intermetallics 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the intermetallics based on the L12-ordered structure are attractive as high temperature structural materials because of their positive temperature dependence of yield strength, "the creep strength anomaly" does not exist in these intermetallics 4 . Large grained B2-ordered NiAl is known to be brittle at room temperature and to have poor creep strength at high temperatures 5 . For NiAl, significant improvements in creep strength were first demonstrated by forming a two phase mixture of NiAl and Ni2AlTi (Heusler phase), although this mixture is still extremely brittle at room temperature 6 .…”
Section: Introductionmentioning
confidence: 99%